Trivalent Gd-DOTA reagents for modification of proteins. Issue 116 (11th November 2015) - Fisher, Martin J.; Williamson, Daniel J.; Burslem, George M.; Plante, Jeffrey P.; Manfield, Iain W.; Tiede, Christian; Ault, James R.; Stockley, Peter G.; Plein, Sven; Maqbool, Azhar; Tomlinson, Darren C.; Foster, Richard; et al.
Abstract : The development of novel protein-targeted MRI contrast agents crucially depends on the ability to derivatise suitable targeting moieties with a high payload of relaxation enhancer without losing affinity for the target proteins. Abstract : The development of novel protein-targeted MRI contrast agents crucially depends on the ability to derivatise suitable targeting moieties with a high payload of relaxation enhancer ( e.g., gadolinium(iii ) complexes such as Gd-DOTA), without losing affinity for the target proteins. Here, we report robust synthetic procedures for the preparation of trivalent Gd-DOTA reagents with various chemical handles for site-specific modification of biomolecules. The reagents were shown to successfully label proteins through isothiocyanate ligation or through site-specific thiol–maleimide ligation and strain-promoted azide–alkyne cycloaddition.